Analisis Kesalahan Berbahasa dan Tanda Baca Teks Berita pada Artikel Detik.com Edisi Februari 2024 sebagai Kelayakan Bahan Bacaan dan Sumber Informasi - Yesica Mai Tuwanti Br Purba; Yessi Ine Rahmandhani; Nadya Fransiska Julianti; Akhmad Faqih Khaerussani; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Didi Pramono (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
News text is information about things that have happened, presented in various forms such as print media, broadcast, and the Internet, so the news must use language that can be understood by the general public so that the news can be conveyed well and there are no misunderstandings in interpreting the information. existing news. The aim of this research is to describe and imply language and punctuation errors in the February edition of detik.com online news text. In this research, a method used to analyze language errors involves an approach, namely quantitative descriptive. Research data collection techniques are the listening method and the note-taking method. This research also uses the collection method and uses formal methods. Based on the research results, language errors in the February edition of detik.com online news text consist of language errors such as several sentences that are difficult to understand, punctuation errors such as a lack of commas, periods, and other punctuation marks, as well as the use of capital letters and morphological errors. The benefit of this research for society is that it can increase the insight of writers and readers, and it can increase knowledge of information that does not yet exist, namely information related to education. The data taken in this research is an analysis of language errors and punctuation in news texts in the February 2024 edition of detik.com articles as appropriate reading materials and sources of information.